Pengaruh Earning Per Share, Debt To Equity Ratio dan Price Earning Ratio Terhadap Harga Saham Perusahaan Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2013 – 2017 - Agustinus, Arie; Firdausy, Carunia Mulya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this research is to find out the influence of Earning Per Share, Debt to Equity Ratio, and Price Earning Ratio on the stock price of food and beverage companies listed in the Indonesia Stock Exchange for the period 2013 to 2017. The research sample consists of 12 companies, that were selected by using a purposive technique sampling method for the period of 2013-2017. The method to analyse the research questions was by using the statistical method of multiple linear regression method. The result found that Earning Per Share and Price Earning Ratio partially have significant influences on the stock price. Whilst Debt to Equity Ratio partially doesn’t have a significant influence. However, Earning Per Share, Debt to Equity Ratio, and Price Earning Ratio have joint effects on the stock price of the food and beverage companies. The coefficient determination of this model was found to be about only 21,9%. This suggests that the three independent variables underestimated have a lack of explanatory power of the stock price of food and beverage companies. Hence, further studies to seek other independent variables in the model are suggested to improve the model underestimated.